When does brand matter more than our senses?: The influence of touching or smelling experience on product evaluation - Garcia-Marques, Teresa (2021)
Submitted by Paulo Pinhão Nunes (pnunes@ispa.pt) on 2021-01-20T11:03:57Z No. of bitstreams: 1 AP 38(2), 141.pdf: 2389872 bytes, checksum: fdf72fa88cf9058d1413110cdd3d7699 (MD5)